Composition and coagulation capacity of holstein and girolanda cow's milk - Tavanti, Vanessa Karoline (2013)
This study aimed to compare centesimal composition, pH, titrable acidity and rennet coagulation capacity of Holstein and Girolanda cow's milk. The milk of 15 animals of each breed was collected 2 to 3 months after the lactation beginning. The milk of Girolanda animals showed higher lipids and total solids contents than the Holsteins one (p0.05). The milks did not have significant difference in the other evaluated parameters. In these conditions, the Girolanda's milk is interesting to lipid basedproducts manufacture and can have larger yield in the processing of dairy products such as cheeses, milk powder, cream and butter than the Holstein's milk.